2019
DOI: 10.1038/s41598-019-49803-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DPP-IV Inhibitors on Glycemic Variability in Patients with T2DM: A Systematic Review and Meta-Analysis

Abstract: Glycemic variability (GV) has been an emerging target for preventing complications related to type 2 diabetes. For reducing GV, DPP-IV inhibitors have shown effectiveness compared to other oral anti-hyperglycemic drugs (OADs), but systematic evaluation has yet to be existed. A systematic review and meta-analysis of randomized controlled trials (RCTs) were performed to evaluate the effect of DPP-IV inhibitors compared with other OADs, on GV as measured by mean amplitude of glycemic excursions (MAGE). Searches w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…In addition, glycemic fluctuations might contribute to poor cognitive outcomes [43]. On the other hand, compared with other oral antidiabetic agents, especially sulfonylureas, DPP-4i provides steady glucose variability [44,45]. Accordingly, our study results demonstrate the independent benefits of DPP-4i use in preserving the cognitive function of patients with diabetes.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, glycemic fluctuations might contribute to poor cognitive outcomes [43]. On the other hand, compared with other oral antidiabetic agents, especially sulfonylureas, DPP-4i provides steady glucose variability [44,45]. Accordingly, our study results demonstrate the independent benefits of DPP-4i use in preserving the cognitive function of patients with diabetes.…”
Section: Discussionmentioning
confidence: 63%
“…Although SGLT-2 inhibitors and GLP-1 agonists were more effective against GV fluctuations than other drugs, certain aspects must be elucidated. A meta-analysis revealed that dipeptidyl peptidase IV inhibitor (DPP-4) inhibitors were significantly more effective than other oral antihyperglycemic drugs at reducing GV in patients with type 2 diabetes [ 39 ]. However, the effects of DPP-4 inhibitors on cardiovascular outcomes are considered neutral [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that dipeptidyl peptidase IV inhibitor (DPP-4) inhibitors were significantly more effective than other oral antihyperglycemic drugs at reducing GV in patients with type 2 diabetes [ 39 ]. However, the effects of DPP-4 inhibitors on cardiovascular outcomes are considered neutral [ 39 , 40 , 41 ]. This could lead to reasonable doubt about the effect of GV on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one recent study assessed the prognostic signi cance of GV calculated from HbA1c vs that calculated from FBS and found that GV parameters calculated from FBS readings were more consistent with the metabolic outcomes and complications (10). There also are statistical considerations and methodological considerations (33). However, in an attempt to relate the results obtained in this study to a reference method, the ALLHAT study suggested that VIM is possibly the most robust measure of GV insofar as each unit change in VIM was associated with a higher risk of death; HR 1.014 (95% CI 1.006-1.022)(P = 0.001)(8).…”
Section: Improvement In Gc: What Is a Clinically Signi Cant Drop In Hba1c?mentioning
confidence: 99%